Upaya Hukum Pasien Melakukan Gugatan Keperdataan terhadap Kesalahan Rekam Medis (Diagnose) Dokter - Siti Nurhayati (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
The medical record is made by health personnel, but the ownership of the medical record is in the hands of the patient. among others; A) the patient may easily know his or her long-term health level on the basis of information provided by the health worker, b) the patient will be able to agree, allow (informid consent), or reject medical treatment, c) the patient can be critical and objective In the course of treatment if no suspicion of malpractice is suspected, d) because the medical record is made at the cost of the patient, it is appropriate that the patient's medical record, and e) with this medical record is expected to arise a partnership relationship between patient and health worker in order to improve health service. Compulsory medical record law to patients is a duty of health personnel in order to perform its duty to respect the patient's right to obtain medical information that is in him. The compulsory norm of medical record law is, in essence, a reciprocal health information information between the patient and the health worker who is the result of the work of a functional team who must obtain the protection of health law. Thus, there is clearly a principle of patient protection as well as health care workers on the principles of patient protection as well as health care workers on their legal principles, and this will be a complex issue if there is a duplication of legal knowledge that the patient is deemed to be the same as a consumer and the health worker is regarded as the perpetrator business. So the relationship between patient and health worker is a relationship having social function and social obligation approach that the relationship should be kept away from consumerism and commercialism